Kepuasan Pelanggan dan Loyalitas Konsumen: Sebuah Literature Review Sistematik terhadap Faktor Penentu dan Hubungannya dalam Konteks Pemasaran Modern - Fatimatul Hasanah; Dzurriyatus Sa’diyah M.; Mu’alimin Mu’alimin (Jurnal Pendidikan Dirgantara, 2025)
Customer satisfaction and consumer loyalty are critical issues in modern marketing management, as they play a strategic role in retaining customers and increasing company profitability. With the increasing intensity of business competition, it has become crucial for scientists and practitioners to understand the components that influence customer satisfaction and their impact on loyalty. The purpose of this study is to systematically review the relationship between customer satisfaction and consumer loyalty, as well as to identify the main determinant factors.The research questions are: (1) What are the most influential factors affecting customer satisfaction and loyalty? (2) How is the relationship pattern between satisfaction and loyalty based on previous research findings?. A systematic literature review was conducted using articles from Google Scholar and Publish or Perish (PoP) with keywords consumer satisfaction, consumer loyalty, service quality, price, and customer trust. A total of 27 articles published between 2020 and 2025 were analyzed, and 5 relevant articles were selected for in-depth review. The findings indicate that product quality, service quality, price, trust, and brand image are dominant factors influencing customer satisfaction and loyalty. In conclusion, future research can explore digital and technology-based service contexts as well as more complex mediation and moderation relationships to deepen understanding of customer satisfaction and loyalty.